A stochastic model for bus injection in an unscheduled public transport service. (April 2020) - Morales, Diego; Muñoz, Juan Carlos; Gazmuri, Pedro
Highlights: An injection stochastic model based on the headway distribution second moment is proposed. An expression for the optimal headway threshold triggering the injection is proposed. A model to determine when a bus should be injected within the headway was developed. We identify at which moment within the headway a bus should be injected. Simulations with real data are used to test the proposed model, proving its accuracy. Abstract: Randomness affecting the operation of public transport systems generates significant increments in waiting times. A strategy to deal with this randomness is bus injection, in which buses are kept in specific points along the route ready to be dispatched when an event such as an extremely long headway occurs. In this work, a stochastic model based on the second moment of the headways distribution is developed to determine if one or more buses are worth reserving for injection in a public transport service. A single stop approach is initially used to determine an expression for the optimal headway threshold triggering the injection. Then, a model for the complete service is developed and used to determine when the empty bus should be injected within the headway once the decision to inject it has been taken. We show that the bus should be injected approximately when 57% of the headway has passed. Simulations with real data are used to test the proposed model, proving its accuracy in terms of measuring the impact on waiting times. The results show that reserving a bus to be injected can be better than operating the entire fleet continuously.